Identifying Barriers to Estimating Carbon Release From Interacting Feedbacks in a Warming Arctic - Treharne, Rachael; Rogers, Brendan M.; Gasser, Thomas; MacDonald, Erin; Natali, Susan (Frontiers in Climate, 2022)
The northern permafrost region holds almost half of the world’s soil carbon in just 15% of global terrestrial surface area. Between 2007 and 2016, permafrost warmed by an average of 0.29°C, with observations indicating that frozen ground in the more southerly, discontinuous permafrost zone is already thawing. Despite this, our understanding of potential carbon release from this region remains not only uncertain, but incomplete. SROCC highlights that global-scale models represent carbon loss from permafrost only through gradual, top-down thaw. This excludes ‘pulse’ disturbances – namely abrupt thaw, in which frozen ground with high ice content thaws, resulting in subsidence and comparatively rapid ongoing thaw, and fire – both of which are critically important to projecting future permafrost carbon feedbacks. Substantial uncertainty remains around the response of these disturbances to ongoing warming, although both are projected to affect an increasing area of the northern permafrost region. This is of particular concern as recent evidence indicates that pulse disturbances may, in some cases, respond nonlinearly to warming. Even less well understood are the interactions between processes driving loss of permafrost carbon. Fire not only drives direct carbon loss, but can accelerate gradual and abrupt permafrost thaw. However, this important interplay is rarely addressed in the scientific literature. Here, we identify barriers to estimating the magnitude of future emissions from pulse disturbances across the northern permafrost region, including those resulting from interacting disturbances. We draw on recent advances to prioritise said barriers and suggest avenues for the polar research community to address these.